(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The importance of understanding adolescent to make a productive citizen who can contribute for his/her family, society, overall the country, has been recognized by psychologists. The present study focused on social undermining and aggression of adolescents according to the types of adolescents and levels of education. Among the 144 adolescents (student respondents) included in this study 72 were orphans and 72 were non-orphan adolescents (each group constituted 36 secondary students and 36 college students). Bangla version of the Social Undermining Scale (Ilyas and Hossain 2007) and Bangla version of the Measure of Aggressive Behavior (MAB) scale (Rahman 2003) were used to measure social undermining and aggressive behavior of adolescents, respectively. The social undermining score clearly indicated that orphan adolescents were significantly of more social undermining (t = 5.32, df = 142, p < .05) over non-orphan adolescents. However, there was no significant difference between secondary and college adolescents. On the other hand, orphan adolescents had significantly more aggression (t = 4.17, df = 142, p < .05) over non-orphan adolescents and secondary adolescent students had significantly more aggression (t = 3.47, df = 142, p < .05) than college adolescent students. Furthermore, the social undermining was positively correlated with aggression (r = .19, p < .05). The Chittagong Univ. J. B. Sci., Vol. 10(1&2):01-13, 2020.